Development of UHF patch antenna for medical communication services / Muhammad Syafiq Mohd Zaman - Mohd Zaman, Muhammad Syafiq (2017)
The study of an Ultra High Frequency (UHF) patch antenna using slots method is designed. The operating frequency that is needed to operate for this antenna is 400MHz. The design was simulated by Computer Simulation Technology Microwave Studio (CST MWS). To prove the proficiency of the antenna, measurement for Return Loss, Gain, Voltage Standing Wave Ratio (VSWR) and Bandwidth using Vector Network Analyzer (VNA) has been done. Specifications of the FR-4 substrate must be same as simulations which is 1.6mm thickness and 4.3 dielectric constant. As results from simulation, the proposed antenna managed to shrink down up to 53.5% size compared to conventional approach. It also shows the improvement of 41.54% of return loss. The proposed patch antenna designed will be suggested to use in Medical Communication Service.